The effectiveness Intensive Short-Term Dynamic Psychotherapy in Defensive style changes and Emotional cognitive cohesion In patients with depression - Habiba, Mohammad; Arab, Ali (Iranian Journal of Neurodevelopmental Disorders, 2023)
Introduction and purpose: due to the presence of depression disorder and its growing trend and the important effects it has on people’s mental and physical health and different aspects of their lives. The present study aims to investigate the effectiveness of short-term dynamic psychotherapy in the changes of defense styles and cognitive-emotional coherence in patients with depression. Method: The current research design is a semi-experimental pre-test-post-test type with a control group. The statistical population of the research includes all the patients referred to psychiatric centers and psychological and counseling services, who are in the age range of 18 to 50 years. The sample people were selected from among the clients of patients with abundant psychological diseases and were assigned to two groups of 15 people for testing and control. The diagnosis of the patients was based on the psychiatric clinical interview and Beck-2 depression questionnaire. The data collection tool is Anders Defense Styles Questionnaire (DSQ-40), Cognitive Emotion Regulation Questionnaire (CQ) and Beck Depression Questionnaire-2. Data were analyzed with SPSS version 26 software and covariance test. Findings: According to the findings of the research, with the help of these treatments, it is possible to help people with injuries to change their defense styles from underdeveloped and neurotic to developed defensive styles and instead of using the strategies of regulating emotions, more than the compromised strategies. user. This arrangement can also help to improve and reduce their complications. Conclusion: The results showed that short-term dynamic stress psychotherapy has a favorable effect on changes in defensive styles and the level of cognitive-emotional coherence of patients affected by the effects.